2019
DOI: 10.1088/1361-6463/ab2495
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced magnetism in SiC

Abstract: Defect induced magnetism, which can be controllably generated by ion or neutron irradiation, is attracting intensive research interest. It not only challenges the traditional opinions about magnetism, but also has some potential applications in spin-electronics. SiC is a new candidate for the investigation of defect-induced ferromagnetism after graphitic materials and oxides due to its high material purity and crystalline quality [1, 2]. In this contribution, we made a comprehensive investigation on the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…However, it has been reported in the literature as well as observed by us that even pure 3C-SiC display ferromagnetic response at RT due to defects present in it [23]. But the magnetic moment value is at least 3 orders of magnitude smaller than that of the Ni-doped samples.…”
Section: B Magnetization Studiesmentioning
confidence: 67%
See 1 more Smart Citation
“…However, it has been reported in the literature as well as observed by us that even pure 3C-SiC display ferromagnetic response at RT due to defects present in it [23]. But the magnetic moment value is at least 3 orders of magnitude smaller than that of the Ni-doped samples.…”
Section: B Magnetization Studiesmentioning
confidence: 67%
“…As pure SiC exhibits defect-induced weak magnetism which cannot scale into the entire volume, there have been studies on p-type carrier doping to enhance the strength of d 0 magnetism. In addition to introducing p-type carriers if the dopant also carries a magnetic moment then it may be an added advantage [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al reported that the intrinsic antisite defects resulted in the magnetism in Bi 2 Te 3 . As reported in the literatures, magnetism can be induced by lattice defects in many materials, which is called “defect-induced magnetism” or “d 0 magnetism”. Furthermore, with the doping of FM elements, intrinsic vacancies could strengthen the coupling between FM dopants, leading to an enhanced FM ordering .…”
Section: Resultsmentioning
confidence: 94%
“…The subject is heavily documented in the case of oxides, nitrides and semiconductors, for thin films or nano-objects (e. g., nanoparticles, tubes, ribbons, …). [30][31][32] The most common cases are oxygen or nitrogen vacancies. Carbon vacancies or 'dangling bonds' in materials such as graphene are also known to induce magnetism.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples of materials becoming magnetic upon presence of extrinsic ( e. g ., Fe atoms in Pt) or intrinsic defects. The subject is heavily documented in the case of oxides, nitrides and semiconductors, for thin films or nano‐objects ( e. g ., nanoparticles, tubes, ribbons, …) [30–32] . The most common cases are oxygen or nitrogen vacancies.…”
Section: Discussionmentioning
confidence: 99%